2005
DOI: 10.1093/cercor/bhi119
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Development of the Primate Visual Cortex, as Revealed by Neurofilament Immunoreactivity: Early Maturation of the Middle Temporal Area (MT)

Abstract: It has been suggested that the development of the cerebral cortex reflects its hierarchical organization, with the primary sensory areas being the first to reach structural and functional maturity, and higher-order association areas being the last. In the present study, we labelled the cortex of New World marmoset monkeys of late fetal and early postnatal ages with an antibody to non-phosphorylated neurofilament, a marker of structural maturation of a subset of pyramidal cells. Supporting the concept of hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
157
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(183 citation statements)
references
References 70 publications
26
157
0
Order By: Relevance
“…The existence of a restricted time window for blindness to lead to functionally specific cross-modal plasticity in right dorsal regions is consistent with previous evidence of early structural (Gogtay et al, 2004;Bourne and Rosa, 2006;Flom et al, 2009) and functional (Ellemberg et al, 2002;Fine et al, 2003;Gregory, 2003;Maurer et al, 2005) maturation of these regions. Our results also support the recent findings of Bedny et al (2010) who, focusing on hMT + /V5, reported that this region reacts more strongly to an auditory condition with higher motion content (approaching footsteps) than to a condition with lower motion content (tones increasing in intensity), in early-onset blind individuals but not in a group of five late-onset blind individuals.…”
Section: Discussionsupporting
confidence: 90%
“…The existence of a restricted time window for blindness to lead to functionally specific cross-modal plasticity in right dorsal regions is consistent with previous evidence of early structural (Gogtay et al, 2004;Bourne and Rosa, 2006;Flom et al, 2009) and functional (Ellemberg et al, 2002;Fine et al, 2003;Gregory, 2003;Maurer et al, 2005) maturation of these regions. Our results also support the recent findings of Bedny et al (2010) who, focusing on hMT + /V5, reported that this region reacts more strongly to an auditory condition with higher motion content (approaching footsteps) than to a condition with lower motion content (tones increasing in intensity), in early-onset blind individuals but not in a group of five late-onset blind individuals.…”
Section: Discussionsupporting
confidence: 90%
“…This relatively direct afference has been hypothesized to mediate residual vision after lesions of the geniculostriate pathway (Rodman et al, 2001). There are, in fact, several intriguing parallels between area MT and the primary sensory areas of the primate cortex, suggesting that, from developmental and evolutionary points of view, area MT could also be considered a "primary visual area" (Bourne and Rosa, 2006). The present study reports on the distribution of cells expressing different immunocytochemical markers in area MT of the marmoset, a species of New World monkey.…”
mentioning
confidence: 72%
“…The long time course might correspond to the prolonged process of myelination and local circuit formation in primate cortex as revealed histologically and with magnetic resonance imaging (Rodman, 1994;Condé et al, 1996;Gogtay et al, 2004;Kourtzi et al, 2006;Malkova et al, 2006;Deoni et al, 2011). Interestingly, area MT like primary sensory areas shows adult-like immunohistochemistry within the first postnatal month (Bourne and Rosa, 2006). In the motor system conduction velocity becomes adult-like only at 11 months of age (Armand et al, 1994).…”
Section: Maturation Of the Optokinetic Reflex And Not-dtnmentioning
confidence: 97%